EXPRESSION OF SYNONYMS IN ENGLISH AND UZBEK LANGUAGES - Mamatova Nilufar Yorkinovna (Galaxy International Interdisciplinary Research Journal, 2024)
This article investigates the expression of synonyms in both English and Uzbek, noting the parallels and variations in how synonymous connections are expressed in each language. Synonyms serve an important function in language, providing speakers with different words to communicate the same or related ideas. This research examines and contrasts the usage of synonyms in English and Uzbek, providing insight into how these linguistic occurrences are used and understood in both languages. By diving into the complexities of synonym usage in these two dissimilar language systems, this study hopes to improve our knowledge of linguistic variety and language expression.